Comparative Study Application of Amicus curiae (Friends of The Court) In Criminal Courts In Indonesia and The United States - Ghiffary, Hafidz Akbar; Umami, Lisa (MIH FH UNSOED, 2025)
Amicus Curiae (friend of the court) refers to a third party, not directly involved in litigation, who voluntarily offers legal opinions or insights relevant to a case in order to assist the court in its deliberations. This practice has long been recognized and systematically regulated in common law jurisdictions, particularly in the United States. In contrast, Indonesia—operating under a civil law system—has begun to incorporate the use of Amicus Curiae in several criminal cases, despite the absence of formal and standardized procedural rules. This legal study aims to analyze the application of Amicus Curiae in the Indonesian context and to compare its implementation in the criminal justice systems of Indonesia and the United States. Employing a normative and comparative juridical approach, this research is grounded in normative legal methodology and relies primarily on secondary data obtained through comprehensive literature review and presented systematically. The study identifies two key findings: first, although Indonesia lacks explicit legal provisions regulating Amicus Curiae, its application has been permitted in certain criminal cases based on the authority granted under Article 5(1) of Law No. 48 of 2009 on Judicial Power; second, in contrast to the United States, Indonesia does not possess a codified framework that clearly governs the submission and evaluation of Amicus Curiae briefs. In light of these findings, this paper argues for the urgent need to develop standardized legal guidelines for Amicus Curiae in Indonesia, in order to ensure consistency, transparency, and legal certainty within the criminal justice process. Keywords: Amicus Curiae; Civil Law System; Common Law System.